Beyond Fertilizers and Labor: Understanding Socioeconomic Drivers of Technical Efficiency Among Smallholder Oil Palm Farmers - Tengku Dede Rachma Sari; Diana Chalil; Lindawati Lindawati (Universitas Pattimura, 2026)
The productivity of independent smallholder oil palm farmers remains significantly lower than that of corporate plantations, despite operating under similar agroecological conditions. This study aims to analyze the socioeconomic factors influencing technical efficiency among independent smallholders, focusing on the roles of education, farming experience, access to extension services, and household income. Using a quantitative explanatory design, the research applies the Cobb-Douglas Stochastic Frontier Analysis (SFA) model based on primary survey data from 125 smallholders in Dolok Masihul District, North Sumatra. Data were analyzed using Frontier 4.1 and STATA through a one-step procedure to assess the effects of socioeconomic characteristics on inefficiency. Results show an average technical efficiency of 0.78, suggesting a 22% potential output increase through better resource utilization. Land size and fertilizer use significantly enhance productivity, while labor and seed type exhibit moderate effects. Farming experience, education, and extension access significantly reduce inefficiency, whereas age and household size have no notable influence. The study’s novelty lies in integrating an econometric model with a sociological perspective, demonstrating that smallholder efficiency is shaped by social capacities rather than agronomic factors alone. It advances a socio-econometric framework for understanding smallholder productivity and recommends policy interventions emphasizing human capital, farmer education, and community-based extension systems to foster sustainable rural development.